Hipotensi Berhubungan dengan Kejadian Post Operative Nausea and Vomiting pada Pasien Pasca Anestesi General dan Anestesi Sub Arahnoid Block - Sugianto, Sugianto; Bakar, Abu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to identify decreased blood pressure and postoperative nausea and vomiting (PONV) in patients post general anesthesia and sub-arachnoid block (SAB) anesthesia. The research method used is descriptive statistics. The study showed a relationship between hypotension and the incidence of PONV in patients receiving general anesthesia, as indicated by the results of the contingency coefficient test, which had a significant value of 0.018. The study's results also showed a relationship between hypotension and the incidence of PONV in patients receiving SAB anesthesia, as indicated by the results of the contingency coefficient test, which had a significant value of 0.027. In conclusion, there is a relationship between a decrease in blood pressure and the incidence of PONV in patients who received general anesthesia and SAB anesthesia at Aisyiyah Bojonegoro Hospital. Keywords: General Anesthesia, Hypotension, PONV, Sub Arachnoid Block (SAB)